MODEL OF INCREASING CORPORATE VALUE BASED ON GOOD CORPORATE GOVERNANCE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK ExCHANGE In 2012-2016 - Alfiatul Wardah; Nunung Ghoniyah (UNISSULA, 2017)
This study aims to analyze the role of Good Corporate Governance (GCG) as a moderating variable in increasing corporate value in manufacturing companies with variables of Corporate Social Responsibility (CSR) disclosure, Profitability, Intellectual Capital (VAICTM) with moderating variables of Good Corporate Governance (GCG) proxied institutional ownership in manufacturing companies listed on the Stock Exchange in 2012-2016. This study is included in a causative study. The population of this study is a manufacturing company listed on the Stock Exchange in 2012-2016 by using purposive sampling technique. There are 25 companies that meet the criteria as a sample so that the 110 data samples were tested using the eviews 10 student application. The results of this study state that the disclosure of Corporate Social Responsibility (CSR) has a significant positive effect on corporate value, profitability has a significant positive effect on corporate value, Intellectual capital (VAICTM) has a positive and insignificant effect on the value of the company, the Corporate Social Responsibility (CSR) disclosure moderated by institutional ownership has a significant negative effect on the corporate value. With more than 50% institutional ownership, the possibility of a public response to CSR disclosure is low, profitability moderated by institutional ownership has no significant positive effect on corporate value, intellectual capital (VAICTM) moderated by negative institutional ownership are not significant. In the findings of this study, VAICTM did not have a significant effect on the corporate value so VAICTM was considered not important. The absence of additional performance due to the absence of standards for measuring intellectual capital in Indonesia. The market may appreciate other factors such as profit and other fundamental factors.Keywords: Corporate Social Responsibility (CSR), profitability, intellectual capital (VAICTM), Good Corporate Governance (GCG), Corporate Value.